Characterization of Apoptotic Parasites for the Identification of Novel Target Molecules in the Treatment of Leishmaniasis - Bergmann, Michaela; Justus Liebig University Giessen (My University, 2021)
Through the bite of an infected sand fly, the parasitic infectious agent Leishmania is transmitted to its mammalian host where it causes the neglected tropical disease leishmaniasis. Since up to date, there is neither a satisfying drug to treat the disease nor a protective vaccination available against the parasite, new options for disease containment are urgently needed. In former studies, it could be shown that Leishmania undergo programmed cell death (apoptosis) while showing the same phenotypic characteristics as mammalian cells. However, none of the genes that regulate apoptosis in Moreover, it was demonstrated that apoptotic Leishmania are crucial for disease development and that this is probably due to phosphatidylserine (PS) moieties, which are presented on the cell surface of dead parasites. Correspondingly, I hypothesize that the identification of novel apoptosis-involved proteins reveals potential new targets for drug or vaccine development. For this purpose, I investigated the efficiency of the selected compounds staurosporine, miltefosine, harmonine and 1o to induce apoptosis in the Leishmania promastigote and amastigote life stage. Here, I could see clear differences of the substances in both stages. Further, I used the compounds to induce apoptosis and to subsequently identify and quantify differently regulated proteins during this process by label-free quantitative mass spectrometry (MS). I was able to identify 55% of the L. major promastigote proteome, quantifying 4416 proteins in promastigotes and 2376 in amastigotes. Focusing on apoptosis-inducing conditions, I found 15 up- and 189 downregulated proteins in promastigotes and 455 up- and 633 downregulated proteins in amastigotes. Within these differently regulated proteins, I expect potential targets for the further understanding of apoptosis mechanisms and it might contain promising drug targets. The proteins elongation factor 1 , p1/s1 nuclease, polyubiquitin and 40S ribosomal protein S2 were upregulated in all apoptosis-inducing conditions tested. To prove my assumption that these proteins are involved in apoptosis, I used CRISPR/Cas9 technology to generate the respective gene knockouts of the identified targets and assessed their apoptosis characteristics. For none of these four targets, a full knockout could be achieved, suggesting an important role of these proteins for parasite survival. Apart from that, I also expanded the range of putative apoptosis-regulating targets to those described in already published research data. My results indicate a new role of the ATP-binding cassette transporter, ABCG2, in the defense against reactive oxygen species. In addition, the importance of the endonuclease EndoG in DNA fragmentation was shown. Moreover, EndoG and the metacaspase MCA have substantial function in the survival of the parasite inside the mammalian host cell. Focussing on the anti-inflammatory potential of PS by MS, we could demonstrate the presence of specific PS species only on apoptotic promastigotes, preliminary data using exosomes suggests that apoptotic parasites derived PS might indeed induce an anti-inflammatory immune response. Altogether, this work provides a very valuable MS dataset and new CRISPR/Cas9 tools increasing our knowledge on apoptosis mechanisms in Leishmania. It has the potential to reveal new drug target candidates, which are linked to cell death in the parasite as well as enabling the development of a vaccine strain.
Keywords: Leishmania; Apoptosis; ddc:500; ddc:570